Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction. (28th June 2019) - Plets, Ruth M. K.; Callard, S. Louise; Cooper, J. Andrew G.; Kelley, Joseph T.; Belknap, Daniel F.; Edwards, Robin J.; Long, Antony J.; Quinn, Rory J.; Jackson, Derek W. T.
Abstract: The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal abp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal abp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal abp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.